PENERAPAN MODEL PEMBELAJARAN INKUIRI BERBANTUAN MEDIA LEAFLET UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS VII SMP NEGERI SATAP WAITAMA - Wohangara, Sulastri; Tamu Ina, Anita; Louise Makatita, Audrey (Universitas Cokroaminoto Palopo, 2024)
This study aims to descript the application of the inkuri learning model with the help of leaflet media in improving the learning outcomes of students at SMP Negeri Satap Waitama. This type of research is an action research of Kemis & Taggar design classes with a descriptive quantitative approach. With the subject of the research, namely class VIII students totaling 30 students. The techniques and instruments for data collection are through tests and psychomotor assessment rubrics. results of the cognitive realm before using the use of the inquiry learning model in the pre-cycle pre-test of students who completed 23.33%, then in the post test of students who completed 50% and then in the first cycle of the pre-test of students who completed 33.33% and in the post test of 90% of students who completed then in the second cycle of students who completed 66.66% Then there was an increase in the post test to 100% of students who completed it. It can be concluded that the inquiry learning model assisted by leaflet media can improve learning outcomes. students who completed it. It can be concluded that the inquiry learning model assisted by leaflet media can improve learning outcomes.